Literasi Keuangan, Teknologi Keuangan, Dan Pengelolaan Keuangan Pribadi : Pengujian Efek Interaksi Locus Of Control - Sapitri, Elsi Nanda; Wendy, Wendy; Syahputri, Anggraini; Azazi, Anwar; Mustika, Uray Ndaru (Jurnal Multidisiplin, 2025)
This study aims to evaluate how financial literacy, financial technology utilization, and financial management are influenced by personal control center as an interaction factor. Participants in this study were active students of the Economics and Business study program at Tanjungpura University, Pontianak City. The sampling technique used purposive sampling technique through questionnaires. The analysis technique used in this research is regression analysis with moderator effects with the help of the Smart-PLS version 4.0 statistical tool. The amount of data analyzed came from 273 respondents. The findings of this study indicate that financial literacy and technology play a positive and significant role in the ability of individuals in individual financial management. Personal control center was found to strengthen the relationship between financial literacy and personal budgeting ability.